Pemanfaatan Digitalisasi Untuk Meningkatkan Pendapatan Pelaku Usaha Mikro (UMK) Perempuan Di Lorong Wisata Kota Makassar - Sapriyadi, Sapriyadi; Syaiful, Muhammad; Wakiya, Nur (Benefit: Jurnal Manajemen dan Bisnis, 2023)
This study aims to find out how the use of digitization is carried out by female MSE actors in the tourist alley, and to find out how it impacts income. This study uses a quantitative descriptive and explanative quantitative approach. The analytical method uses ordinal logistic regression. The results showed that the marketing digitization and product distribution digitalization variables had no significant effect on changes in income. Meanwhile, the financial digitization variable has a significant effect on changes in income. Female MSEs in the tourist aisle who have not used financial digitization have decreased income opportunities by 0.126, stagnant income opportunities by 0.495, and income opportunities increased by 0.378. Meanwhile, female MSEs who have used financial digitalization have decreased income opportunities by 0.027, stagnant income opportunities by 0.212, and income opportunities increased by 0.761. This means that female MSE actors in the tourist aisle who have used digitalization of finance have smaller and stagnant income opportunities and have greater opportunities for increased income compared to female MSE actors who have not used financial digitalization.